The effect of increasing levels of palm kernel meal containing α-β-mannanase replacing maize to growing-finishing hybrid duck on growth performance, nutrient digestibility, carcass trait, and VFA - Sjofjan, O.; Adli, D. N.; Natsir, M. H.; Nuningtyas, Y. F.; Bastomi, I.; Amalia, F. R. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
In this experiment, we investigated the effect of increasing levels of palm kernel meal containing α-β-mannanase replacing maize to growing-finishing hybrid duck on growth performance, nutrient digestibility, and carcass trait. One hundred and ninety- six hybrid ducks [(Peking x Khaki Campbell)] with 410.52 ± 95.25 g BW) were allotted to 5 dietary treatments with 9 ducks (unsexed) per pen and 4 replicates per treatments. These dietary treatments were: NC (negative control; maize-soybean-meal based diet), PKM25 (maize replacement with PKM α-β-mannanase 25%), PKM50 (maize replacement with PKM α-β-mannanase 50%), PKM75 (maize replacement with PKM α-β-mannanase 75%), PKM100 (maize replacement with PKM α-β-mannanase 100%). There was a curve linear decrease in the growing phase and finisher phase in feed intake as the level of α-β-mannanase palm kernel meal increased in the diet. Curvilinear, the result was presented no significant difference (P>0.05) on the initial body weight, growing and finishing phase body weight. The result of this study showed the used α-β-mannanase in the palm kernel meal presented a significant difference (P < 0.05) on the nutrient digestibility of dry matter and crude protein. Furthermore, Carcass traits showed the reflection in line with the final weight and internal organs were better to compare to control 0.5% using α-β-mannanase in the palm kernel meal. In summary, the increase of the level of palm kernel meal with α-β-mannanase enzyme was had a positive effect on the hybrid ducks and the replacement of palm kernel meal by 25% with the addition of the α-β-mannanase enzyme was able to improve digestibility and reduce abdominal  fat of hybrid ducks.